Analisis komunikasi persuasif pengasuh asrama di Pondok Pesantren At Tibyan Deli Serdang - Suhendri Suhendri (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research aims to analyze persuasive communication carried out by dormitory caretakers at Pondok Pesantren At Tibyan Deli Serdang in shaping the character and faith of students. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and documentation with data analysis teachniques using data reduction, data display and data conclusion The results showed that the dormitory caretakers at Pondok Pesantren At Tibyan Deli Serdang used several persuasive communication techniques, including using language that is easy to understand, providing examples, and linking the message conveyed with the students' life context. In addition, the dormitory caretakers also pay attention to psychological and social factors of the students in carrying out persuasive communication. However, there are still several factors that affect the effectiveness of persuasive communication, such as language proficiency limitations and a lack of understanding of communication psychology.